Civil War Monuments and the Militarization of America - Brown, Thomas J., 1960- (Book collections on Project MUSE., 2019)
"This ... assessment of Civil War monuments unveiled in the United States between the 1860s and 1930s argues that they were pivotal to a national embrace of military values. Americans' wariness of standing armies limited construction of war memorials in the early republic ... and continued to influence commemoration after the Civil War. ... distrust of standing armies gave way to broader enthusiasm for soldiers in the Gilded Age. Some important projects challenged the trend, but many Civil War monuments proposed new norms of discipline and vigor that lifted veterans to a favored political status and modeled racial and class hierarchies. A half century of Civil War commemoration reshaped remembrance of the American Revolution and guided American responses to World War I"--